2017
DOI: 10.3390/en10121992
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Environmental Kuznets Curve in the EU Agricultural Sector through an Eco-(in)Efficiency Index

Abstract: Studies on agricultural production practices advance within international literature and new methods are proposed in order to assess the agricultural sustainability, either at farm or macro level. The present paper builds on these advancements and develops a synthetic Eco-(in)efficiency index by employing a directional distance function-data envelopment analysis (DEA) model. This index is used in order to assess the sustainability of the EU agricultural sector for the period 1999-2012 on a country level. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…In the relationship of income and CO 2 emissions, Lau et al [20] and Churchill et al [21] analyzed a panel of OECD countries and landed Energies 2018, 11, 3462 3 of 15 on the same conclusion that these economies are illustrated a mechanism similar to the EKC in play. While, Vlontzos et al [22] found an N-shape relationship between Gross Domestic Product (GDP) and emissions in EU agriculture sector, Urban and Nordensvard [23] could find the evidence of EKC hypothesis for four out of five Nordic countries. Arango-Miranda et al [24] could not find the existence of the EKC hypothesis at all in a mixed panel of 10 developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In the relationship of income and CO 2 emissions, Lau et al [20] and Churchill et al [21] analyzed a panel of OECD countries and landed Energies 2018, 11, 3462 3 of 15 on the same conclusion that these economies are illustrated a mechanism similar to the EKC in play. While, Vlontzos et al [22] found an N-shape relationship between Gross Domestic Product (GDP) and emissions in EU agriculture sector, Urban and Nordensvard [23] could find the evidence of EKC hypothesis for four out of five Nordic countries. Arango-Miranda et al [24] could not find the existence of the EKC hypothesis at all in a mixed panel of 10 developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 94%
“…For European countries, we found quite few such studies. For Spain, the relations between per capita CO 2 emissions and per capita income was studied, and an inverted U-shaped form was obtained using cointegration and a non-inverted U-shape as methodologies for instability tests [49]; the relationship between GHG emissions and GDP was considered as the main variable of climate change, and the environmental Kuznets curve was analyzed for the relationship between greenhouse gases and the main aspects of economic development on panel data of groups of countries in the EU [50,51]; the impact of agro-economic factors on GHG emissions in Southeastern Europe was analyzed in comparison to advanced European economies, confirming the EKC hypothesis, which is an inverted U-shaped relation between per capita GDP and carbon dioxide emissions [52]; the effects of renewable energy and non-renewable energy, real income and trade openness on CO 2 emissions for EU countries were analyzed, obtaining different shapes for the EKC curve [53]; the Kuznets hypothesis was examined for the G20 group by introducing other variables-trade openness, the ratio of secondary industry value-added to GDP and population density-and concluded that the hypothesis was verified for developing countries and failed for developed countries [21]; the relationship between economic growth, greenhouse gas emissions, energy taxes and R&D was investigated based on panel data of 22 countries of the EU [54]; and it was demonstrated that the GHG-GDP relationship in terms of sustainable agricultural production in EU countries looks rather like an N-shaped curve [55]. As a result of the analyzes performed, statistical evidence in favor of the existence of an EKC for CO 2 emissions per capita in relation to GDP per capita was not found for 16 EU countries [16].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…At an international level, some researchers examined TFEE for the European agricultural sector [13][14][15][16]. Some other studies compare the energy efficiency across countries within China.…”
Section: Literature Reviewmentioning
confidence: 99%